Unilateral pityriasis rosea on the same site of previous eccrine hidradenitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Vasodilation, however induced, is an important localization factor even in dermatology. In children, a characteristic vasodilation occurs in the diaper area, due to the increased temperature induced by the external plastic. The vasodilation is implicated in the localization in this site of a great number of lesions in the course of infections such as varicella, constitutional diseases such as diaper psoriasis and proliferative disorders (2) such as Langerhans cell histiocytosis (Fig. 3). Another characteristic site of vasodilation in the child is the scalp: this explains the localization to the scalp in the first months of life of atopic dermatitis and also of Langerhans cell histiocytosis (Fig. 4). The vasodilation induced by vaccination may be responsible for an earlier localization of generalized infections such as chickenpox (3). The vascular lesions of the child may constitute a localization factor for psoriasis, atopic dermatitis (Fig. 5) and acne and may sometimes explain an asymmetric localization of these usually symmetrical skin disorders. The vasodilation of actinic erythema may be responsible for a greater concentration of exanthema lesions but also of acne - Mallorca acne (Fig. 6) - in the photoexposed sites (3). The vasodilation of atopic dermatitis and psoriasis can act as a localization factor for viral infections such as chicken pox, herpes simplex, coxsackiosis, molluscum contagiosum. You should also consider that when in a given site an intense vasodilation occurs, especially when persistent, a trivial thermal or other stimulus can later cause a much more intense vasodilation in that area than elsewhere. The current case seems to indicate that this tendency towards easier vasodilation persists for a long time.